Desarrollo e implementación de una aplicación web para el Gobierno Autónomo Descentralizado Municipal de Machala, para la gestión de consultas, tasas e impuestos municipales, registros de la propiedad y generación de reportes estadísticos para la toma de decisiones. - Reyes Pineda, Walter Paúl (2014)
In order to improve service to citizens of Machala and meet the needs of automation of information with respect to taxes this project for Decentralized Autonomous Government (GAD) Municipal Machala entitled "Development and implementation of an application is developed web for Decentralized Autonomous municipal Government of Machala, management consultation, municipal fees and taxes, property records and generation of statistical reports for decision-making. ".